Pendidikan Islam berbasis Adiwiyata di MAN I Mojokerto: Implementasi dan Normativitas Qur’ani - Thobroni, Ahmad Yusam; Masyithoh, Dewi (State Islamic Institute of Madura, 2020)
Environmental damage occurs due to human actions or natural events. To prevent humanity from being destructive, awareness of environmental preservation needs to be fostered through education. This article aims to discuss the relationship between human and environmental perspective of the Koran. MAN I Mojokerto became the subject of this research using the theory of developing ecological citizenship with the Talcot Parsons system approach, which was then reviewed with the perspective of the Koran to find its relevance. The results showed that the environmental education (PLH) based on Adiwiyata in MAN I Mojokerto was well implemented, manifested in the level of policy, curriculum, action activities, and fulfillment of facilities and infrastructure. The implementation of this PLH has strong relevance to the teachings of the Koran about environmental preservation, which lies in the understanding that; because man is the caliph of Allah, he is tasked with prospering the earth and its environment. As a consequence, he must carry out the mandate to prosper the earth, in addition to having the right to use the environment for the benefit of his life, he also has an obligation to preserve it.